ENT 530 Social Media Portfolio: Le Santoir / Siti Afiqa Jalil @ Ali - Jalil @ Ali, Siti Afiqa (2021)
Le Sautoir is a start-up business that sells variety of necklaces. Hence, it is under product and services. Le Sautoir is a sole proprietorship business form and operating as a small business. The business utilizes Facebook page to connect with people and establish its presence. Le Sautoir started the business around October 2020, it then gained engagements with more people on Facebook. The concept of the business is to provide specialty products to the customers who are into accessories especially necklaces. It sells necklaces taken from supplier in a limited number of stocks. The items chosen are based on the quality, comfortable to those who wear it and most importantly is trendy necklaces. In addition, Le Sautoir’s mission is to exceed customer's satisfaction and provide necklaces that are contemporary, fashionable and elegant to wear. Whereas its vision is to add sparkle and confidence in people’s everyday life. For the product price, it is best to say that the necklaces are reasonable and not to mention affordable. The target market is focused on mainly female of all ages who have strong interest in fashion. As for the market potential location, it is based in Shah Alam, Selangor. However, the business is expected to grow as it mainly implement the social media platform to engage with more audience throughout Malaysia.